Ring-augmented versus conventional one-anastomosis gastric bypass: Perioperative and short-term results in the randomized controlled RiMini trial - Maureen Tissink; Josien Timmerman; Marloes Vermeer; Tim Verhagen; Ian Faneyte; Eric Hazebroek; Marc van Det (PLoS ONE, 2026)
Purpose Recurrent weight gain remains a challenge in metabolic bariatric surgery (MBS). Recent publications focused on ring-augmented Roux-en-Y gastric bypass (RYGB) and ring-augmented sleeve gastrectomy (SG), but few studies have addressed the potential of ring-augmentation for one-anastomosis gastric bypass (OAGB). Objectives The RiMini trial is a single-center randomized controlled trial that investigates the difference in long-term weight reduction, associated medical comorbidities, quality of life, and procedure-related adverse events of ring-augmented OAGB compared to conventional OAGB in adult patients eligible for primary OAGB. This analysis reports the trial’s short-term outcomes, including the peri-operative safety of the procedure, short-term adverse events, and weight outcomes at one year postoperatively. Methods Between July 2022 and December 2023, a total of 214 patients (107 per group) underwent either ring-augmented or conventional OAGB after randomization. Peri- and postoperative adverse events, and total and excess weight loss percentages (%TWL and %EWL) were assessed by intention-to-treat and per-protocol analysis. Results At baseline, there were no differences between groups regarding age, gender, and body mass index (BMI). Mean operation time was 51 minutes (±13) in both groups (p = 0.84). One patient in each group experienced a perioperative complication (p = 1.00; 0.9%). There was no significant difference in postoperative minor (Clavien Dindo (CD) 1–2) (p = 0.68) or major (CD3–5) (p = 0.77) complications. In the first year, two Minimizer rings were electively removed at patients’ request, without observed complications related to the ring. At one year, mean BMI was comparable in both groups (28 kg/m 2 ). There was no statistically significant difference between ring-augmented and conventional OAGB in %TWL (33% vs 31%; p = 0.30), and %EWL (86% vs 84%; p = 0.45). Conclusions The 1-year analyses of the RiMini trial showed that ring-augmented OAGB is comparable in safety to conventional OAGB. At 1 year, there was no statistically significant difference in weight loss between the groups.